Appreciative inquiry - lessons learned from virtual teams. (4th July 2019) - Elam, Debora A.; Brands, Kristine M.
Technology continues to expand research opportunities and access to information previously constrained by resource limitations. Without effectively utilising technology, researchers and practitioners could be limiting their potential to impact positive change. This paper describes some learnings from a review of the current literature regarding the use of technology in appreciative inquiry (AI), as well as learnings from other fields in which technology has been used to bring people together in a virtual environment, and how technology can be applied to improve the richness of data to effectively impact change. This paper then describes some recommendations for AI researchers and practitioners, and identifies some additional areas for continued research in virtual AI studies.